O tributilestanho induz anormalidades no tecido adiposo mamário e atrofia glandular mamária em ratas - Costa, Charles Santos da (2019)
Tributyltin (TBT) is an obesogen associated with several complications. However, few investigations have evaluated TBT effects on adult mammary glands (MG). In this investigation, we assessed whether TBT's obesogenic effects resulted in abnormal MG fat pad expansion and other irregularities. TBT was administered to female rats, and their MG morphophysiological development was assessed. We further assessed the MG fat pad for PPAR , ER , and aromatase protein expression, as well as inflammation, oxidative stress (OS) and fibrosis. Irregular MG morphological development such as lower TEB number, alveolar (AB), lobule and differentiation (DF) escore were observed in TBT rats. TBT rats had abnormal MG fat accumulation as evidenced by increased numbers of hypertrophic adipocytes, triglyceride (TG) levels and PPAR expression. A strong negative correlation between the MG obesogenic makers and TEB number, AB and DF escore were observed in TBT rats. MG inflammation was observed in TBT rats. A positive correlation between the MG obesogenic markers and inflammation were observed. High ER and aromatase expression were observed in MG of TBT rats. MG OS and fibrosis were present in the TBT rats. Additionally, a positive correlation between the MG obesogenic markers and OS were observed in TBT rats. Thus, these data suggest that obesogenic TBT effects led to MG irregularities in the adult female rats.